The Evolution of Territorial Conquest After 1945 and the Limits of the Territorial Integrity Norm. (2020) - Altman, Dan
Abstract: Past studies conclude that a territorial integrity norm caused territorial conquest to decline sharply after 1945, virtually subsiding after 1975. However, using new and more comprehensive data on territorial conquest attempts, this study presents a revised history of conquest after 1945. Unlike attempts to conquer entire states, attempts to conquer parts of states remained far more common than previously recognized. More than conquest declined in frequency, its relationship with war evolved. Challengers attempting conquest before 1945 often initiated a war, then sought to occupy large territories. Today, challengers more often seize small regions, then attempt to avoid war. Adopting this strategy, the fait accompli, challengers increasingly came to target territories with characteristics that reduce the risk of provoking war—such as a low population and the absence of a defending military garrison—but challengers nonetheless take a calculated gamble. In part because seizures of smaller territories with such characteristics have not declined, the operative constraint appears to be against war-prone aggression, not territorial revision. The evolution of conquest is a symptom of war's decline, not its cause. Most of the evidence that the territorial integrity norm suppressed conquest or war withers under investigation with new data. Attempts to get away with seizing small pieces of territory are likely to be a defining element of the twenty-first-century international security landscape.